2008
DOI: 10.1021/jf072581i
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Potential of Glyphosate Formulations: Mode-of-Action Investigations

Abstract: A broad array of in vitro and in vivo assays has consistently demonstrated that glyphosate and glyphosate-containing herbicide formulations (GCHF) are not genotoxic. Occasionally, however, related and contradictory data are reported, including findings of mouse liver and kidney DNA adducts and damage following intraperitoneal (ip) injection. Mode-of-action investigations were therefore undertaken to determine the significance of these contradictory data while concurrently comparing results from ip and oral exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Glyphosate was reported to induce 8-OHdG adducts in liver but not kidney tissues whereas a GBF (with an equivalent level of glyphosate) was reported to induce 8-OHdG adducts in kidney but not in liver tissue. Results of the Bolognesi et al (1997) study are contradicted by another published study (Heydens et al 2008) that was not considered by IARC. In this study no statistically significant increases in 8-OHdG were observed in liver or kidneys of mice 24 h after treatment by i.p.…”
Section: Indirect Measures Of Oxidative Stress Vs Measures Of Oxidatmentioning
confidence: 90%
See 1 more Smart Citation
“…Glyphosate was reported to induce 8-OHdG adducts in liver but not kidney tissues whereas a GBF (with an equivalent level of glyphosate) was reported to induce 8-OHdG adducts in kidney but not in liver tissue. Results of the Bolognesi et al (1997) study are contradicted by another published study (Heydens et al 2008) that was not considered by IARC. In this study no statistically significant increases in 8-OHdG were observed in liver or kidneys of mice 24 h after treatment by i.p.…”
Section: Indirect Measures Of Oxidative Stress Vs Measures Of Oxidatmentioning
confidence: 90%
“…Moreover, the GBF was administered i.p. using dimethylsulfoxide (DMSO) as a vehicle and the use of this vehicle and route has unusual toxicity properties (Heydens et al 2008). This assay was also unusual in that doseresponsive increases were observed at multiple sampling times, which is difficult to explain since cells damaged at early sampling times have usually died and disappeared from the bone marrow by later sampling times.…”
Section: Chromosomal Effects In Vivomentioning
confidence: 99%
“…The authors suggested that subtoxic concentrations of H 2 O 2 that occur in the cell due to presence of xenobiotics may lead to the genotoxic effects. However, Heydens et al [2008] showed no significant increase in the amount of 8-OHdG, despite kidney values being 143% higher than control values. Comparing the tail intensity values for both comet assay versions (Table II and III), at all tested concentrations, we obtained higher statistical differences between treated and untreated cells for the alkaline comet assay than for the hOGG1 modified comet assay.…”
Section: Discussionmentioning
confidence: 63%
“…A published toxicity study has reported that use of a DMSO/olive oil vehicle by the i.p. route dramatically enhanced the toxicity of glyphosate formulation or the formulation components without glyphosate compared to saline vehicle (Heydens et al, 2008). The enhanced toxicity observed with this vehicle was not observed when the oral route was used.…”
Section: Micronucleus and Chromosomal Aberrationmentioning
confidence: 94%
“…Heydens et al (2008) reported on studies in mice to further investigate toxic effects and 8-OHdG levels associated with the routes, vehicles and dose levels of the earlier studies. The Heydens et al (2008) publication reported significant GBF-induced liver and kidney toxicity for high i.p. doses but no liver or kidney toxicity for comparable oral doses.…”
Section: Glyphosate-based Formulationsmentioning
confidence: 99%